Lietuviško atviruko pirmtakas - Kaunas, Domas (Knygotyra, 1998)
The forerunner of the European postcard was the small 19th century illustrated greeting card which was printed on light cardboard. These cards contained either drawings of towns or landscapes, or portraits of well-known persons. They were given on various occasions to another person, mailed in envelopes, or collected in albums. This fashionable publication soon reached the Lithuanians. Cards of this type, with Lithuanian text and coloured drawings, were first produced in 1888 by the well-known Lithuanian author and luminary in the Lithuanian national movement of East Prussia, Vilius Kalvaitis (1848–1914). This publication consisted of two sets of six cards each – one set in Gothic and the other in Latin characters, which were printed, in chromolithography, by the printer H. Grossmann in Berlin. They were sold by booksellers, including Vilius Kalvaitis, who had a bookstore in Tilžė (Tilsit). This printing was completely sold out by 1898 and became a rarity. It was seen for the last time in 1900 at the World Exhibition in Paris where organizers of the Lithuanian section displayed both sets. Later mention of these illustrated cards in various literature as well as bibliographies was very incomplete, but the author of this article has been able to correct some historical inaccuracies, having recently discovered several cards from each set. Based on these cards, as well as other reliable sources, it can be stated that some of the cards had citations from the Bible, some had church hymns (eg. the poet of German Enlightenment F. Gellert), others had secular poems.The illustrations were of garlands and ornamental wreaths. Some cards had comments in the Finnish language, handwritten, it is believed, by the specialist in Lithuanian philology A. R. Niemi, who was recording Lithuanian songs and hymns in the district of Tilžė in 1910–1912. The first traditional Lithuanian postcards in East Prussia appeared in 1905 and were very similar to the earlier illustrated cards published by Vilius Kalvaitis.